Investigation on the solid-oxide fuel cell/desalination - Lai, Yawei (2014)
Solid Oxide Fuel Cell-Gas Turbine (SOFC-GT) system and Multi-Stage Flash distillation (MSF) play roles in supplying electricity and water. Thus, it could be reasonable to consider a hybrid system which utilizes wasted gas from SOFC-GT to desalinate seawater. Till now, there are few researches studying such a system with both SOFC-GT and MSF involved. In order to discuss and verify its system performance, a steady-state SOFC-GT-MSF model was developed. In this project, firstly a standalone MSF model was established based on a selected MSF distillation plant studied by A. Sabah Abdul-Wahab[1]. Then a simple heat exchanger model was built for heat recovery. Lastly system integration was conducted to combine an existing SOFC-GT model and the MSF model. Simulation results of the SOFC-GT-MSF model indicated that by consuming wasted gas, such a system could have similar performance as compared to traditional MSF system. The findings also suggest that it may be feasible to use the SOFC-GT-MSF system for efficient and clean power and water production. For more accurate results, other specified data should be collected from the MSF distillation plant to avoid approximation and, a larger SOFC-GT model is desired so to minimize inaccuracy caused by system scaling and integration.